Late HIV/AIDS diagnosis among people living with HIV in Wuhan in 2023 - Tang, Li; Du, Yan-Tao; Kong, Wen-Hua; Liu, Pan; Zhu, Ze-Rong; Xie, Shi-Zhe; Liu, Man-Qing (Frontiers in Microbiology, 2025)
Late HIV diagnosis is defined as presenting for care with a CD4 count <350 cells/μl or an AIDS-defining event, and it continues to be a significant challenge in the global effort to prevent and control HIV/AIDS. To examine the late diagnosis of HIV in Wuhan, we retrospectively analyzed cases of late diagnosis among newly identified people living with HIV in 2023. Of the 383 newly diagnosed individuals with HIV infection, 260 (67.89%) were diagnosed late and their CD4 counts were less than 350 cells/μl. Among them, 135 (35.25%) had advanced HIV disease, with CD4 counts below 200 cells/μl. Compared to those diagnosed promptly, the population with late HIV diagnosis had a higher viral load, older age, and lower CD/CD8 ratio. They were also more likely to be men who have sex with men (MSM) or farmers, and were typically diagnosed through voluntary counseling and testing (VCT) or clinical patients. These findings highlight the high rate of late HIV diagnosis in Wuhan, suggesting the need for more attention and more targeted measures toward earlier diagnosis within the population.